Towards Legal Coherence in Trademark Law and Investment Law of Asean Countries Post AEC (Asean Economic Community) Blueprint 2025 - Tomi Suryo Utomo (Fakultas Hukum Universitas Islam Indonesia, 2018)
The blueprint of the ASEAN Economic Community (AEC) 2025 is adopted by ASEAN members on November 22, 2015. To discuss this issue, this paper focused on analyzing any challenges in achieving legal coherence in terms of brand and trade among the ASEAN countries and analyzing the principles and strategies to create legal coherence in terms of brand and investment laws in ASEAN countries. This was a normative research using statute approach and law comparison that analyzed secondary data qualitatively. This paper concluded that legal coherence in brand and investment laws can be achieved if ASEAN could overcome various challenges such as differences in legal, economic and technological systems, legal culture and infrastructure development. The principles required are the harmonization of laws and policies to abolish trade barriers related to borders. Some of the strategies of legal coherence are to make Blueprint as a guideline and to apply harmonization of law through standardization and technical regulation reformation.